Copyright or Right-To-Copy? Towards the Proper Balance between Freedom of Expression and Copyright in Cyberspace - Irina V. Shugurova; Mark V. Shugurov (Centre for Behaviour and Wellness Advocacy, 2016)
This article examined the renewed theoretical approaches to seeking the proper balance between the human right to freedom of expression, opinion and information on the one hand, and copyright on the other hand. This analysis was done with regard to the context of current information society's digital environment. This article showed that the way of striking a renewed balance between the two is by reforming the existing copyright law. It is recommended that, an upgraded copyright law must be able to prevent the tensions between exclusive rights and the right to freedom of expression.